Satisfaction and acceptability of cabotegravir long-acting injectable suspension for prevention of HIV: Patient perspectives from the ECLAIR trial. Issue 4 (4th July 2018) - Murray, Miranda I.; Markowitz, Martin; Frank, Ian; Grant, Robert M.; Mayer, Kenneth H.; Hudson, Krischan J.; Stancil, Britt S.; Ford, Susan L.; Patel, Parul; Rinehart, Alex R.; Spreen, William R.; Margolis, David A.
Abstract : Background: Cabotegravir (GSK1265744) is an integrase strand transfer inhibitor in development as a long-acting (LA) intramuscular injectable suspension for HIV-1 pre-exposure prophylaxis (PrEP). Objective: We report participant outcomes from the phase IIa ECLAIR study related to tolerability, acceptability, and satisfaction of cabotegravir LA. Methods: The ECLAIR study (ClinicalTrials.gov identifier, NCT02076178) was a randomized, placebo-controlled study in healthy men not at high risk of acquiring HIV-1. Participants were randomized (5:1) to once-daily oral cabotegravir 30 mg or placebo tablets for 4 weeks, followed by gluteal intramuscular injections of cabotegravir LA 800 mg or saline placebo every 12 weeks. The primary objective was to evaluate the safety of cabotegravir LA over three injection cycles (to Week 41). Secondary objectives assessed the tolerability, satisfaction, and acceptability of cabotegravir LA. Results: Among 115 participants who received injections in the cabotegravir ( n  = 94) and placebo ( n  = 21) groups, 93% ( n  = 87) and 95% ( n  = 20) completed the injection phase, respectively. Injection intolerability led to withdrawal in 4 participants (4%) receiving cabotegravir LA. The most frequently reported Grade ≥2 adverse event was injection-site pain. Most participants (74% [ n  = 67]) receiving consecutive injections favored cabotegravir LA vs oral cabotegravir. Most participants were satisfied with cabotegravir LA (75% [ n  = 64]), were willing to continue (79% [ n  = 68]), and would recommend (87% [ n  = 75]) the therapy. Conclusions: While Grade ≥2 injection-site pain was common, most participants reported overall satisfaction with and preference for cabotegravir LA, with few discontinuations due to injection intolerance. These findings support investigation of cabotegravir LA as an alternative to daily oral PrEP regimens.